Sport bodies: An examination of positive body image, sport-confidence, and subjective sport performance in Jamaican athletes. (July 2023) - Ricketts, Chelsi; Malete, Leapetswe; Myers, Nicholas D.; Bateman, André G.; James Bateman, Caryl
Abstract: Guided by the Sport-Confidence Model, this study examined the associations among a positive body image, sport-confidence, and sport performance evaluations. Using a cross-sectional design, a purposive sample of 314 Jamaican athletes (male = 70.7%; M a g e = 22.85; SD = 4.89) completed measures of body and functionality appreciation, sport-confidence, and subjective sport performance. Results from path analysis provided evidence for good model-data fit. Body ( B = 9.03, p < .001) and functionality ( B = 4.93, p = .036) appreciation exerted direct effects on sport-confidence. Sport-confidence exerted a direct effect on sport performance evaluations ( B = 0.09, p < .001). Body ( B = 0.79, CI95% [0.44, 1.17]) and functionality ( B = 0.43, CI95% [0.05, 0.92]) appreciation exerted indirect effects on sport performance evaluations through sport-confidence. Results indicate that supporting the development of a positive body image in athletes may contribute to feelings of sport-confidence and positive performance outcomes. Highlights: Body appreciation had a positive direct effect on sport-confidence. Functionality appreciation had a positive direct effect on sport-confidence. Sport-confidence had a positive direct effect on sport performance evaluations. A positive body image was indirectly related to performance via sport-confidence.